Three stilbenes make difference to the antifungal effects on ochratoxin A and its precursor production of Aspergillus carbonarius. (May 2022) - Cai, Xinyu; Qi, Jianrui; Xu, Zhe; Huang, Lingxuan; Li, Yihan; Ren, Xueyan; Kong, Qingjun
Abstract: The present study demonstrated the toxic effects of stilbenes on fungi, which were related to the structures of the stilbenes. Pterostilbene with methoxy had the best antifungal properties, followed by piceatannol, which has a catechol structure, and finally resveratrol. The inhibitory effects of stilbenes at 0.1, 0.2, 0.4, 0.8, 1.6 mM on A. carbonarius mycelia growth and spore germination were assessed by plate inhibition tests and poisoned food technique. Predicted by SPSS software, the IC50 values of resveratrol, piceatannol, and pterostilbene were 5.10, 1.80, and 0.28 mM, respectively. In addition, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) showed that 0.4 mM pterostilbene treatment induced incompleteness of the sporangium and distortion of the mycelial structure. Antitoxic activities of stilbenes were positively correlated with their antifungal activities. 1.6 mM pterostilbene suppressed OTA synthesis better (63.48%) than 1.6 mM piceatannol (25.91%) and 1.6 mM resveratrol (22.98%). Furthermore, in the presence of stilbenes, the examined biosynthetic genes, and regulatory factors like NRPS, PKS, LaeA, HAL, bZIP, and P450 were remarkably downregulated to reduce OTA/OTB production. Increased levels of total stilbenes in grapes after fungal infestation can slow down the increased rate in OTA levels. It indicated stilbenes could be used as naturally safe and efficient compounds in food active packaging or preservatives against OTA in food. Graphical abstract: Image 1 Highlights: Three stilbenes' antifungal effects: pterostilbene > piceatannol > resveratrol. OTA inhibitory capacities had a positive correlation with their antifungal activities. The reduction of OTA production was related to the downregulation of OTA synthesis pathway genes by stilbenes. The changes in OTB content were consistent with OTA. A. carbonarius infection induced the accumulation of total stilbenes and OTA.